Experimental study on anchorage performance of rockbolts by adding steel aggregates into resin anchoring agents. - Ming Zhang (Public Library of Science (PLoS), 2021)
Pull-out testing was carried out to evaluate the effects of shape, size and concentration of steel aggregates on anchorage performance. Steel grit with particle sizes of 1.5, 2.0, and 2.8 mm and steel shot diameters of 1.4, 2.0, and 2.5 mm were used as steel aggregates and were added into the resin anchoring agent. For each kind of steel aggregate, either 30, 40 or 50 aggregates were used to evaluate the effects of different steel aggregate densities. Anchorage specimens were prepared using ϕ20mm rebar bolts and steel sleeves. Compressive and shear strengths of resin containing steel aggregates, the pullout curve, and the circumferential strain of the sleeves were measured, and the energy consumption was calculated. Results show that compressive and shear strengths of resin containing steel grit and steel shot are increased by 8.4%-17.0% compared to pure resin. For the aggregate numbers of 30, 40 and 50, the anchoring force is increased by 7.9%, 7.5% and 6.5%; energy consumption is increased by 19.2%, 15.0% and 18.6%; and the circumferential strain of the specimen is increased by 28.4%, 25.1% and 39.5%, respectively. The effect of aggregate size on anchoring performance is significant; that is, the aggregate sizes of 1.4~1.5, 2.0 and 2.5~2.8 mm increase the anchoring force, energy consumption and sleeve circumferential strain by 8.5%, 4.6% and 8.7%, 16.0%, 8.4% and 28.4%, and 17.9%, 23.3% and 51.9%, respectively. The relationships of the anchoring force, energy consumption, and circumferential strain with steel aggregate quantity and size are formulated. Results show that the addition of steel aggregates increases the compressive and shear strengths of the resin, and steel aggregate quantity and size have significant impact on anchoring performance. This paper provides the basis for optimization of resin anchoring agents used in the mining industry. The impact of anchoring agent shear strength and residual shear strength on the anchoring effect were also discussed based on the failure analysis of the anchoring section.